Tracking kidney stones in a homogeneous medium using a trilateration approach - Shoar, K; Turney, B; Cleveland, R (Acoustical Society of America, 2017)
Shock wave lithotripsy is a non-invasive procedure by which kidney stones are fragmented by thousands of shock waves. Currently, many shock waves are delivered to the body that do not impact the stone, but do result in tissue trauma. This motivates developing a monitoring system to locate kidney stones, with the goal of gating shock waves not aligned with the stone, and hence, reducing renal trauma during lithotripsy. The system consists of a circular array housing twenty-two 0.5 MHz transducers that can be mounted on a clinical lithotripter. It was deployed in a water tank and tested with two stone models made from gypsum cement and a stone model fragment. An algorithm consisting of threshold detection, automatic rejection of weak signals, and triangulation was developed to determine the location of stones. The results show that within ±15 mm of the focus of the lithotripter, the accuracy was better than 4 mm in the lateral directions and 2 mm in the axial direction. Using off-the-shelf hardware, the algorithm can calculate stone positions every 1 s allowing for real-time tracking during lithotripsy.